Keragaman Cendawan Pascapanen pada Umbi Bawang Merah Varietas Bima Brebes - Okky Setyawati Dharmaputra; Sri Listiyowati; Ira Zahara Nurwulansari (Jurnal Fitopatologi Indonesia, 2018)
Diversity of Postharvest Fungi on Shallot Bulbs Variety Bima BrebesIn Indonesia, shallot (Allium ascalonicum) is horticultural main commodity after hot pepper. Significant yield losses can be caused by postharvest fungi infection. Research on the diversity of postharvest fungi on shallot bulbs has been conducted in some countries, unfortunately little is done in Indonesia. The study was aimed to obtain information on the diversity of postharvest fungi infecting shallot bulbs variety Bima Brebes from several traditional markets in Bogor City. Shallot bulbs were collected in January and February 2016. The study consisted of fungal isolation from shallot bulbs, fungal pathogenicity test, and identification of pathogenic fungi based on morphological and molecular characteristics. Morphology identification was based on the color of fungal colony, growth pattern, as well as somatic and reproduction structures. Several species of pathogenic fungi were successfully identified from shallot bulbs i.e. Alternaria alternata, Aspergillus niger, Colletotrichum gloeosporioides species complex, Fusarium fujikuroi species complex, F. oxysporum, F. solani, Penicillium citrinum and P. pinophilum.  Among these fungi, the highest pathogenicity was shown by C.  gloeosporioides species complex.